The Longman handbook of twentieth-century Europe - Cook, Chris, 1945- (Longman companions to history., 2014)
The twentieth century was one of constant upheaval across Europe. The continent saw wars, revolutions and the collapse of empires and a range of leading figures from Stolypin and Stalin to Chirac, Schroder and Putin. This book provides a detailed yet wide-ranging guide to the turbulent events of twentieth century Europe. Covering the whole period from Tsarist Russia and Imperial Germany to the Balkan Wars of the 1990's and the final birth of the Euro in 2002, it provides a convenient user-friendly compendium of key fact and figures for the whole of Europe - from the Atlantic to the Urals.